A Magnesium‐Enriched 3D Culture System that Mimics the Bone Development Microenvironment for Vascularized Bone Regeneration. Issue 12 (18th April 2019) - Lin, Sihan; Yang, Guangzheng; Jiang, Fei; Zhou, Mingliang; Yin, Shi; Tang, Yanmei; Tang, Tingting; Zhang, Zhiyuan; Zhang, Wenjie; Jiang, Xinquan
Abstract: The redevelopment/regeneration pattern of amputated limbs from a blastema in salamander suggests that enhanced regeneration might be achieved by mimicking the developmental microenvironment. Inspired by the discovery that the expression of magnesium transporter‐1 (MagT1), a selective magnesium (Mg) transporter, is significantly upregulated in the endochondral ossification region of mouse embryos, a Mg‐enriched 3D culture system is proposed to provide an embryonic‐like environment for stem cells. First, the optimum concentration of Mg ions (Mg 2+ ) for creating the osteogenic microenvironment is screened by evaluating MagT1 expression levels, which correspond to the osteogenic differentiation capacity of stem cells. The results reveal that Mg 2+ selectively activates the mitogen‐activated protein kinase/extracellular regulated kinase (MAPK/ERK) pathway to stimulate osteogenic differentiation, and Mg 2+ influx via MagT1 is profoundly involved in this process. Then, Mg‐enriched microspheres are fabricated at the appropriate size to ensure the viability of the encapsulated cells. A series of experiments show that the Mg‐enriched microenvironment not only stimulates the osteogenic differentiation of stem cells but also promotes neovascularization. Obvious vascularized bone regeneration is achieved in vivo using these Mg‐enriched cell delivery vehicles. The findings suggest that biomaterials mimicking the developmental microenvironment might be promising tools to enhance tissue regeneration. Abstract : Inspired by the correlation between MagT1 and embryonic endochondral ossification, an embryonic‐like microenvironment is created for stem cells by fabricating a magnesium‐enriched 3D culture system. Mg 2+ via MagT1 not only stimulates osteogenic differentiation through the mitogen‐activated protein kinase/extracellular regulated kinase (MAPK/ERK) pathway, but also promotes neovascularization. An obvious vascularized bone regeneration is achieved in vivo using the magnesium‐enriched cell vehicles.